Numerical Investigation of Bioaerosol Transport in a Compact Lavatory - Jingyuan Wan (MDPI AG, 2021)
The lavatory is a fertile area for the transmission of infectious disease through bioaerosols between its users. In this study, we built a generic compact lavatory model with a vacuum toilet, and computational fluid dynamics (CFD) is used to evaluate the effects of ventilation and user behaviors on the airflow patterns, and the resulting fates of bioaerosols. Fecal aerosols are readily released into the lavatory during toilet flush. Their concentration rapidly decays in the first 20 s after flushing by deposition or dilution. It takes about 315 s to 348 s for fine bioaerosols (<10 µm in diameter) to decrease to 5% of the initial concentration, while it takes 50 and 100 µm bioaerosols approximately 11 and <1 s, respectively, to completely deposit. The most contaminated surfaces by aerosol deposition include the toilet seat, the bowl, and the nearby walls. The 10 µm aerosols tend to deposit on horizontal surfaces, while the 50 and 100 µm bioaerosols almost always deposit on the bowl. In the presence of a standing thermal manikin, the rising thermal plume alters the flow field and more bioaerosols are carried out from the toilet; a large fraction of aerosols deposit on the manikin’s legs. The respiratory droplets generated by a seated coughing manikin tend to deposit on the floor, legs, and feet of the manikin. In summary, this study reveals the bioaerosol dilution time and the easily contaminated surfaces in a compact lavatory, which will aid the development of control measures against infectious diseases.